Pengaruh Konsentrasi Pupuk Organik Cair Diperkaya Rhizobacteri Osmotoleran terhadap Pertumbuhan dan Hasil Tanaman Padi pada Kondisi Cekaman Kekeringan - Chandra Kurnia Setiawan (Universitas Muhammadiyah Yogyakarta, 2016)
This study aimed to know the best concentration of Liquid Organic Fertilizer enriched with Rhizobacteri Osmotolerance to enhance plant growth and yield of rice in drought stress conditions. This research was conducted using single factor experiment arranged in a completely randomized design (RAL). The treatments tested are concentrations of POC 5 ml / l + NPK fertilizer 50% recommendations, POC concentration of 10 ml / l + NPK fertilizer 50% recommendations, POC concentration of 15 ml / l + NPK fertilizer 50% recommendations, POC concentration of 20 ml / l + NPK fertilizer 50% recommendations, and NPK fertilizer 100% recommendations with three replications. The results showed that Liquid Organic Fertilizer enriched with Osmotoleran Rhizobacter can reduce NPK fertilizers until 50%. Liquid Organic Fertilizer concentration of 15 ml / l + NPK fertilizers 50% tend to improve the growth and production of Ciherang rice in drought stress conditions.